EFEKTIVITAS PENENTUAN PRIORITAS MUSTAHIQ DALAM PROGRAM RUMAH BINAAN LAZ SIDOGIRI - Salim; Maghfur, Ifdlolul; Dayat, M. (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effectiveness of the mechanism for determining the priority scale of mustahiq in the Fostered Housing Development Program (Program Pembangunan Rumah Binaan/PRB) implemented by LAZ Sidogiri in Rembang District. The study is motivated by the high demand for adequate housing assistance among low-income communities, which is not proportional to the limited availability of zakat funds. Therefore, an objective, accountable, and well-targeted selection mechanism is required. This research employed a qualitative approach with a descriptive-evaluative design. Data were collected through document analysis, literature review, and examination of relevant studies related to zakat distribution and housing assistance programs. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings indicate that the priority determination mechanism has been implemented systematically through administrative verification, field surveys, and beneficiary selection. The mechanism is considered sufficiently effective in directing assistance to mustahiq with inadequate housing conditions and urgent needs. However, several challenges remain, including limited and non-integrated data systems, the absence of standardized assessment indicators, and the potential subjectivity of field survey officers during the evaluation process. Furthermore, the Fostered Housing Development Program has contributed positively to improving the beneficiaries’ quality of life, particularly in terms of housing conditions, health, and social welfare. Therefore, strengthening the data management system, standardizing assessment indicators, and enhancing human resource capacity are necessary to improve the accuracy and effectiveness of beneficiary selection in the future.